Local Political Dynamics in Village Head Elections in Damai Village, Sidenreng Rappang Regency, Indonesia - Muh Awalil Resky S; Ahmad Mustanir; Barisan Barisan; Jamaluddin Ahmad; Kittisak Jermsittiparsert (Universitas Muhammadiyah Ponorogo, 2024)
This study aims to determine the dynamics of local politics in the 2021 Election of Peaceful Village Heads in Sidenreng Rappang Indonesia. This research uses a qualitative descriptive method. Data collection techniques used were observation, interviews, field notes, and documentation. Resource persons were selected by purposive sampling. Data analysis namely data reduction, data presentation, and conclusions. Data analysis, namely data reduction, data presentation and conclusions displayed through Nvivo 12 Plus Software visualization. NVivo 12 Plus was chosen because it is capable of producing qualitative text data in the form of attractive data visualizations. The results of this study indicate that the local political dynamics that occurred in the Peace Village head election led to polarization in the village community structure. The election of the village head still leaves a mark in which there has been a rift in relations between the people who still have close family ties. The dynamics occur in three phases, namely pre-election, implementation of the election, and post-election. The behavior of the voting community in Damai Village is still dominated by the behavior of traditional voters. The occurrence of community polarization in Damai Village is the result of the political behavior of the people who are still traditional.